Identification of peptidomimetics as novel chemical probes modulating fibroblast growth factor 14 (FGF14) and voltage-gated sodium channel 1.6 (Nav1.6) protein-protein interactions. Issue 3 (1st February 2019) - Liu, Zhiqing; Wadsworth, Paul; Singh, Aditya K.; Chen, Haiying; Wang, Pingyuan; Folorunso, Oluwarotimi; Scaduto, Pietro; Ali, Syed R.; Laezza, Fernanda; Zhou, Jia
Graphical abstract: Abstract: The voltage-gated sodium (Nav) channel is the molecular determinant of action potential in neurons. Protein-protein interactions (PPI) between the intracellular Nav1.6 C-tail and its regulatory protein fibroblast growth factor 14 (FGF14) provide an ideal and largely untapped opportunity for development of neurochemical probes. Based on a previously identified peptide FLPK, mapped to the FGF14:FGF14 PPI interface, we have designed and synthesized a series of peptidomimetics with the intent of increasing clogP values and improving cell permeability relative to the parental lead peptide. In-cell screening using the split-luciferase complementation (LCA) assay identified ZL0177 (13 ) as the most potent inhibitor of the FGF14:Nav1.6 channel complex assembly with an apparent IC50 of 11 μM. Whole-cell patch-clamp recordings demonstrated that ZL0177 significantly reduced Nav1.6-mediated transient current density and induced a depolarizing shift of the channel voltage-dependence of activation. Docking studies revealed strong interactions between ZL0177 and Nav1.6, mediated by hydrogen bonds, cation-π interactions and hydrophobic contacts. All together these results suggest that ZL0177 retains some key features of FGF14-dependent modulation of Nav1.6 currents. Overall, ZL0177 provides a chemical scaffold for developing Nav channel modulators as pharmacological probes with therapeutic potential of interest for a broad range of CNS and PNS disorders.